Improving the tax e-filing system in Indonesia: An exploration of individual taxpayers’ opinions - Panggah Tri Wicaksono; Christine Tjen; Vitria Indriani (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
The growing number of e-filing users in Indonesia requires a more robust e-filing system, so continuous improvement is essential. This study investigates areas of improvement to the e-filing system by exploring taxpayers’ opinions. An open-ended survey question was used to collect opinions from individual taxpayers who have used the system to file their tax returns. There were 318 respondents who provided answers to the question. This study used qualitative content analysis on participants’ responses about how the e-filing system can be improved. We utilized NVivo 12 qualitative data analysis software to perform coding of participants’ responses. This study employed the three quality dimensions (i.e., system quality, information quality, and service quality) in the updated DeLone and McLean Information Systems (IS) Success Model as a lens to analyze taxpayers’ opinions. The results show that taxpayers are especially concerned about improvements in these areas: access to the system and ease of use (system quality), e-filing guidelines and data security (information quality), and dissemination program (service quality). This study provides recommendations for the Directorate General of Taxes to improve the e-filing system to support taxpayers’ needs optimally.